Interaksi dengan Surah Al-RahmÄn di Pondok Pesantren Al-Manshur Putri Popongan Klaten - Istiqomah, Nurul; Maknun, Moch Lukluil (MAGHZA, 2020)
Living Qur'an is a variety of forms and models of reception practices and community responses in treating and interacting with Qur'an in the midst of community life. The purpose study is to describe how the history and practice of reading the surah Ar Rahman in the Al Manshur Islamic Boarding School Popongan Klaten and to find the meaning tradition of reading the Surah Ar Rahman for those who implement them include caregivers, administrators, and students. To find out more details, the writer uses qualitative research methods to understand what phenomena experienced by research subjects by describing in the form of written or oral words from the implementation of the tradition of reading the surah Ar Rahman. For the method of data collection techniques, the authors use interviews, notes, and documentation. The tradition of reciting surah Ar Rahman has been started since the old generation's predecessor, in 1978. For the way the recitation is done in a quiet voice, it must be polite and tawadlu'. The meaning of reciting surah Ar Rahman is to get syafa'at, facilitate all matters, get sustenance, and always get the blessing of Allah.